2014
DOI: 10.1371/journal.pone.0112976
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+-Induced PRE-NMR Changes in the Troponin Complex Reveal the Possessive Nature of the Cardiac Isoform for Its Regulatory Switch

Abstract: The interaction between myosin and actin in cardiac muscle, modulated by the calcium (Ca2+) sensor Troponin complex (Tn), is a complex process which is yet to be fully resolved at the molecular level. Our understanding of how the binding of Ca2+ triggers conformational changes within Tn that are subsequently propagated through the contractile apparatus to initiate muscle activation is hampered by a lack of an atomic structure for the Ca2+-free state of the cardiac isoform. We have used paramagnetic relaxation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 44 publications
1
23
0
Order By: Relevance
“…25; 29 In the closed state, the switch peptide adopts a helical conformation and binds the hydrophobic cleft of the TnC N , 23 moving approximately 10 Å from its blocked state position. 29 TnI N is also bound to TnC N , 25 and TnI C is bound to tropomyosin but likely in a different conformation. 30 The IR is likely not bound to the thin filament in the closed state.…”
Section: Troponin Conformation During Muscle Contractionmentioning
confidence: 99%
“…25; 29 In the closed state, the switch peptide adopts a helical conformation and binds the hydrophobic cleft of the TnC N , 23 moving approximately 10 Å from its blocked state position. 29 TnI N is also bound to TnC N , 25 and TnI C is bound to tropomyosin but likely in a different conformation. 30 The IR is likely not bound to the thin filament in the closed state.…”
Section: Troponin Conformation During Muscle Contractionmentioning
confidence: 99%
“…This increase in inter-calcium distance was caused by a straightening of the central cTnC helix, leading to an increased distance between NcTnC and CcTnC (see Figure 3B). Experimentally, it has been demonstrated that isolated cTnC takes on a more extended form than cTnC anchored in the cTn complex 38 . Similar trends are observed for the homologous calmodulin protein, for which the Ca 2+ -bound state assumes an elongated conformation that maximally-separates the N- and C-terminal globular domains in absence of a target protein, but subsequently collapses when a target protein is presented 39 .…”
Section: Resultsmentioning
confidence: 99%
“…Since the early 1970s label motion has been modeled in terms of “wobble within a cone” model (Berliner, 1976),(Borbat, McHaourab, & Freed, 2002) or as an excluded volume (Cordina et al, 2014). These non-atomistic models overestimated the label motion, erring on the conservative side.…”
Section: Molecular Modelingmentioning
confidence: 99%
“…The extent of that relaxation enhancement is distance dependent, thus if the label tilts towards one side of the backbone, we expect those residues to be affected more than the residues the spin label tilts away from. We have one case of a spin labeled protein, TnC, for which preNMR was performed using the MTSSL label attached to position 136 (Cordina et al, 2014). The C-terminal domain of TnC is fairly rigid, and we can assume that the backbone structure in the NMR experiments is the same as the structure observed in the crystals.…”
Section: Simulation Strategymentioning
confidence: 99%
See 1 more Smart Citation